Israel vis-à-vis Iran in Syria: The perils of active containment. Iran's growing influence in the evolving order in Syria is driving Israel to change its mindset and strategies - Gil David Murciano (Stiftung Wissenschaft und Politik (SWP), 2017)
The perceived shift from chaos to an evolving order in Syria presents a challenge to Israel's policy of limited intervention. Iran's growing influence in Syria and its efforts to improve Hezbollah's strategic capacities presents Israeli decision-makers with a sense of urgency to act now while the future settlement in Syria is still being shaped in order to avoid a fait accompli of an Iranian stronghold on Israel's northern border. This notion is further enhanced by a perceived lack of a serious commitment from the main extra-regional powerbroker, Russia, as well as the US to Israel's national security needs. During the last few months, the first signs of a change became apparent in Israel's strategic approach as well as a new willingness to take active measures to contain Iran's strategic efforts in Syria. The combination of a new proactive Israeli policy and the lack of a security regime to regulate the situation increases the likelihood of an unintended escalation between the parties. Germany should use its relations and leverage vis-à-vis the two parties to promote a new security regime between Israel and Iran and help prevent a destructive escalation.
Keywords: 320